Existência, multiplicidade e concentração de soluções positivas para uma classe de problemas quasilineares em espaços de Orlicz-Sobolev - Silva, Ailton Rodrigues da (2016)
In this work we establish existence, multiplicity and concentration of positive solutions for the following class of problem 8<: div 2 ( jruj)ru + V (x) (juj)u = f(u); in RN; u 2 W1; (RN); u > 0 in RN; where N 2, is a positive parameter, ; V; f are functions satisfying technical conditions that will be presented throughout the thesis and (t) = Rjtj 0 (s)sds. The main tools used are Variational methods, Lusternik-Schnirelman of category, Penalization methods and properties of Orlicz-Sobolev spaces.